Respuesta :
Answer:
[tex]\left(2+\sqrt{3},9+7\sqrt{3}\right)\; \textsf{and}\;\left(2-\sqrt{3},9-7\sqrt{3}\right)[/tex]
Step-by-step explanation:
Point (2, 3) is on a tangent line to the curve f(x) = x² + 3x - 4.
The slope of the tangent line at any point (x, y) on the curve of f(x) is given by the derivative of f(x) evaluated at x.
Differentiate f(x):
[tex]f'(x)=2x+3[/tex]
So, the slope (m) of the tangent line at any point on the curve f(x) can be found by substituting the x-coordinate of the point into m = 2x + 3.
To find the x-coordinates of the points of tangency, where the tangent line at that point passes through (2, 3), substitute the slope of the tangent line (2x + 3) and the point (2, 3) into the point-slope form of a linear equation:
[tex]y-y_1=m(x-x_1)\\\\y-3=(2x+3)(x-2)\\\\y-3=2x^2-x-6\\\\y=2x^2-x-3[/tex]
Now, set this equation equal to function f(x) to find the x-coordinates of the points of tangency:
[tex]2x^2-x-3=x^2+3x-4\\\\x^2-4x+1=0[/tex]
To solve the quadratic equation, use the quadratic formula:
[tex]\boxed{\begin{array}{l}\underline{\sf Quadratic\;Formula}\\\\x=\dfrac{-b \pm \sqrt{b^2-4ac}}{2a}\\\\\textsf{when} \;ax^2+bx+c=0 \\\end{array}}[/tex]
In this case a = 1, b = -4 and c = 1. Therefore:
[tex]x=\dfrac{-(-4) \pm \sqrt{(-4)^2-4(1)(1)}}{2(1)}\\\\\\x=\dfrac{4 \pm \sqrt{16-4}}{2}\\\\\\x=\dfrac{4 \pm \sqrt{12}}{2}\\\\\\x=\dfrac{4 \pm 2\sqrt{3}}{2}\\\\\\x=2\pm \sqrt{3}[/tex]
So, the x-coordinates of the points of tangency where the tangent line at those points also passes through point (2, 3) are:
[tex]x = 2+\sqrt{3}\\\\x= 2-\sqrt{3}[/tex]
Substitute the found x-values into function f(x) to find the corresponding y-coordinates:
[tex]f(2+\sqrt{3}) = (2+\sqrt{3})^2+3(2+\sqrt{3})-4\\\\f(2+\sqrt{3}) = 7+4\sqrt{3}+6+3\sqrt{3}-4\\\\f(2+\sqrt{3}) = 9+7\sqrt{3}[/tex]
[tex]f(2-\sqrt{3}) = (2-\sqrt{3})^2+3(2-\sqrt{3})-4\\\\f(2-\sqrt{3}) = 7-4\sqrt{3}+6-3\sqrt{3}-4\\\\f(2-\sqrt{3}) = 9-7\sqrt{3}[/tex]
Therefore, the exact points where the tangent touches f(x) are:
[tex]\Large\boxed{\boxed{\left(2+\sqrt{3},9+7\sqrt{3}\right)\; \textsf{and}\;\left(2-\sqrt{3},9-7\sqrt{3}\right)}}[/tex]
[tex]\dotfill[/tex]
Additional Notes
To find the equations of the two tangent lines, substitute the x-coordinates of the points of tangency into the slope formula (m = 2x + 3), then substitute the slope and point (2, 3) into the point-slope form of a linear equation.
Tangent line 1
[tex]m=2(2+\sqrt{3})+3=7+2\sqrt{3}[/tex]
[tex]y-3=(7+2\sqrt{3})(x-2)\\\\y-3=(7+2\sqrt{3})x-14-4\sqrt{3}\\\\\boxed{y=(7+2\sqrt{3})x-11-4\sqrt{3}}[/tex]
Tangent line 2
[tex]m=2(2-\sqrt{3})+3=7-2\sqrt{3}[/tex]
[tex]y-3=(7-2\sqrt{3})(x-2)\\\\y-3=(7-2\sqrt{3})x-14+4\sqrt{3}\\\\\boxed{y=(7-2\sqrt{3})x-11+4\sqrt{3}}[/tex]
![Ver imagen semsee45](https://us-static.z-dn.net/files/df0/edefeb8a28ea70ff716d9e1fcd9a18f6.png)